Charge trap assisted high efficiency in new polymer-blend based light emitting diodes. (March 2016) - Hassan, M.U.; Liu, Yee-Chen; Hasan, Kamran ul; Butt, H.; Chang, Jui-Fen; Friend, R.H.
Abstract: Polymer blend system, F81− x SY x, based on mixture of poly (9, 9-dioctylfluorene) (F8) and a poly ( para -phenylenevinylene) (PPV) copolymer, superyellow (SY), has been proven to be a high performance blend material in polymer light emitting diode (PLED). This blend system exhibits luminance ( L ) >10 4 cd m −2, luminous efficiency ( η ) >21 cd A −1 and low operating voltage ( V ) 3–10 V. The performance can be credited to the large difference ( 0.6 eV) between the highest occupied molecular orbital (HOMO) levels of F8 ( 5.8 eV) and SY ( 5.2 eV), where, SY molecules serve as hole-traps in the F8 host polymer and reduce their mobility. This dictates a balanced charge injection into the emissive layer and results in overall increase in the device performance. Graphical abstract: Highlights: New polymer blend F81- x SY x used as emissive layer in PLEDs exhibit high efficiency. Difference between HOMOs of F8 and SY is exploited to reduce the hole mobility. SY molecules in F8 act as hole traps and dictate the overall transport properties. High efficiency of F81- x SY x based PLEDs is due to the balanced charge transport.